The ghost of capitalism: A guide to seeing, naming and exorcising the spectre haunting the business school. Issue 2 (April 2022) - Kociatkiewicz, Jerzy; Kostera, Monika; Zueva, Anna
The aim of this article is both a pronouncement of doom and an offer of hope for the Western business school. Both come from the recognition that business schools are haunted and that the haunting spectre is none other than the capitalist ideology. We ground our thinking in the established rich 'ghostly' academic literature where the metaphor of the ghost is used to reveal the powerful agency of the unspoken-of and the unseen. Using three fictional ghostly tales as interpretive lenses, we make three arguments. First, we argue that capitalism is a ghost in the walls of the business school. Second, we suggest that capitalism's ghostly nature prevents the business school from offering a curriculum that serves more than the growth of financial capital. Third, we propose that naming of capitalism is integral to the exorcism of its ghost and the creation of curriculum that engages with the social and environmental challenges of our times.